IMMU-04. FIRST-IN-CHILDREN PHASE 1B STUDY USING THE IDO PATHWAY INHIBITOR INDOXIMOD IN COMBINATION WITH RADIATION AND CHEMOTHERAPY FOR CHILDREN WITH NEWLY DIAGNOSED DIPG (NCT02502708, NLG2105). (1st June 2021) - S. Johnson, Theodore; Pacholczyk, Rafal; Aguilera, Dolly; Al-Basheer, Ahmad; Bajaj, Manish; Berrong, Zuzana; Castellino, Robert C; Eaton, Bree R; Esiashvili, Natia; Foreman, Nicholas; Heger, Ian M; Kennedy, Eugene P; et al.
Abstract: Background: Diffuse intrinsic pontine glioma (DIPG) is a uniformly fatal brain tumor with no available cure. Indoximod blocks the IDO (indoleamine 2, 3-dioxygenase) pathway, thereby reversing IDO-mediated immune suppression in the tumor microenvironment. Methods: Patients aged 3 to 21 years with treatment-naive DIPG were eligible for this phase 1b dose-confirmation study of indoximod. The treatment regimen comprised continuous oral indoximod (38.4 mg/kg/day divided twice daily) with conformal photon radiation (54 Gy in 30 fractions), followed by cycles of indoximod with temozolomide (200 mg/m2/day, days 1–5 in 28-day cycles). Results: Thirteen patients (median age 9 years, range 5 to 20 years) with DIPG were treated. Median OS was 14.5 months (follow-up ranged 4.8 to 29.3 months), 12-month OS was 61.5% (8/13), and 18-month OS was 30.8% (4/13), with 1 patient remaining in follow-up at the data cutoff. This compared favorably to expected median OS of approximately 10.8 months, 12-month OS of 45.3%, and 18-month OS of 16.2% taken from published historical data from the Pediatric Brain Tumor Consortium. Two patients showed near-complete responses lasting until relapsing after 7.6 months and 13.3 months of study therapy, respectively. Many patients had increased circulating non-classical monocytes (nc-Monos, CD16+, CD14neg, CD33+, HLA-DR+) within the first 3 treatment cycles, and elevation of this early pharmacodynamic marker was predictive of subsequent OS. Patients with nc-Monos >10% (n=7) had median OS of 19 months, whereas patients with nc-Monos below 10% (n=5) had median OS of 7 months (p=0.0047). No patients stopped therapy for toxicity. The most common indoximod-attributed adverse events were thrombocytopenia, neutropenia, nausea, vomiting, dizziness, and fatigue. Conclusions: Adding indoximod immunotherapy to conventional radiation and chemotherapy for front-line treatment of pediatric patients with DIPG was well-tolerated. Improved outcomes were observed in patients having evidence of pharmacodynamic response. A follow-on phase 2 study is in progress (NCT04049669).